Monitoreo de editoriales y artículos de opinión y la imagen que proyectan del Presidente Rafael Correa. Estudio de caso: diario el comercio abril 2009 - Rivadeneira Moreno, Katerine Elisa (2013)
The objective of this work is to show that the conflict between political power and media power have always existed, since the earliest ways of journalism in Greece and Rome, during the Middle Age, with the invention of printing press, during the French Revolution, with the Industrial Revolution until our times. Conflicts between political power and media power have place all over the world in Europe, Asia, Africa and North America where even neoliberal governments like Barack Obama have problems with Fox and in South America we can see more often this troubles in Argentina, Bolivia, Venezuela and Ecuador. Thereby we can break the idea that Ecuadorian mass media are trying to sell us saying that only in Ecuador and only with the President Rafael Correa have been so many trouble and attacks to the freedom of expression.